Una aproximación a la lírica de Paul Celan - Echagüe, Hugo (ARFIL y UNL, 2018)
It is necessary to specify in which sense the concept “Silence” is to be used in Celan’s poetry. If on one hand it can be said that his Lyric is an answer to Adorno’s impossibility of poetry after Auschwitz, and that it arose in the frame of the annihilation of war and Nazism that also devastated language (Steiner), on the other hand, it is in a dialectical way that this allusion to Silence, neither positively nor factically determinable, could be explored, according to the opposing tension lines that go across Celan’s Lyric.